Islamic Banks and the Role of Economic Empowerment: Study at BSI Ternate on UMKM in Agriculture and Fisheries (Agrikan Jurnal Agribisnis Perikanan, 2024)
Bank Syariah Indonesia (BSI) as an Islamic financial institution based on Islamic Banking must be able to ensure the safety of people in the world and long for a financial economic system that has the value of truth (logic), goodness (ethic), and beauty (aesthetic). The Islamic financial system was born and emerged from a thought that is full of religious character and has special characteristics that are not possessed by other economic and financial systems such as the financial economic idiology of capitalists, socialists, liberalists and communist financial economics. This is due to the perfection of the rules through the elaboration of the concept of muamalah based on Islamic sharia. Muhammad Syafi'i Antonio and Hilman Fauzi Nugraha, that Islamic banking financial institutions and other Islamic financial institutions are recognised today to have become the leading torch in the economic development project and Islamic finance in Indonesia and even in the world. Bank Syariah Indonesia (BSI) continues to support the growth of Micro, Small and Medium Enterprises (UMKM) through the provision of access to Islamic financing. this is reflected in the distribution of BSI financing to the MSME sector nationally until March 2024 has been realised at Rp 46.62 trillion. This research shows that the existence of Islamic banking is expected to be able to synergise with the government in the empowerment of Micro, Small and Medium Enterprises (UMKM).
Keywords: Perbankan Syariah; Pemberdayaan; UMKM